1985
DOI: 10.1016/0741-5214(85)90109-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of needle hole bleeding with ethylcyanoacrylate glue (Krazy Glue)

Abstract: Needle hole bleeding from polytetrafluoroethylene (PTFE) grafts causes blood loss and prolongs vascular procedures. Past studies have shown the cyanoacrylate glues to polymerize rapidly and cause minimal tissue toxicity. This study was undertaken to evaluate the efficacy of ethyl-2-cyanoacrylate glue (Krazy Glue, KG) in obtaining prompt hemostasis in vascular anastomoses in a heparinized canine model. KG effected complete hemostasis in a significantly shorter time than oxidized cellulose and digital pressure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Citrin et al developed a coagulopathic model in mongrel dogs using iv heparin (100 U/kg) given at the start of surgery, which was followed by repeated doses of iv heparin (50 U/kg) during surgery to establish bleeding from needle holes from polytetra ouroethylene (PTFE) grafts anastomosed to femoral arteries [6]. Similarly, Barbalinardo et al administered iv heparin (200 U/kg) initially, followed by repeated doses of iv heparin (50 U/kg) at the end of each hour in experimental bypass surgery using PTFE grafts anastomosed femoro-femoral and carotid-carotid [7].…”
Section: Discussionmentioning
confidence: 99%
“…Citrin et al developed a coagulopathic model in mongrel dogs using iv heparin (100 U/kg) given at the start of surgery, which was followed by repeated doses of iv heparin (50 U/kg) during surgery to establish bleeding from needle holes from polytetra ouroethylene (PTFE) grafts anastomosed to femoral arteries [6]. Similarly, Barbalinardo et al administered iv heparin (200 U/kg) initially, followed by repeated doses of iv heparin (50 U/kg) at the end of each hour in experimental bypass surgery using PTFE grafts anastomosed femoro-femoral and carotid-carotid [7].…”
Section: Discussionmentioning
confidence: 99%
“…The glue effected complete hemostasis in a significantly shorter time than oxidized cellulose and digital pressure in 18-gauge needle holes in PTFE grafts, graft to graft end-to-end anastomoses, and end of graft to side of artery anastomoses. They concluded that cyanoacrylate is highly effective when used as a suture line sealant in PTFE graft anastomoses [14].…”
Section: Figmentioning
confidence: 99%
“…Butyl cyanoacrylate, marketed as Tissu‐Glu (isobutyl‐2‐cyanoacrylate, Ellman, Oceanside, NY) has not been approved for use in the United States. Krazy‐Glue, a short chain CA, has been described in the literature as effective for cutaneous wound closures 16 …”
Section: Physical or Mechanical Agentsmentioning
confidence: 99%
“…Krazy-Glue, a short chain CA, has been described in the literature as effective for cutaneous wound closures. 16 All acrylates are relatively nonreactive, but inflammatory reactions, fibrosis, or neurotoxicity may result after application. 2 Acrylates have been used for cutaneous wounds and injuries to soft tissue [17][18][19] and bone, 20 as well as sealing cerebrospinal fluid leaks.…”
Section: Acrylatesmentioning
confidence: 99%